Enhanced electrical properties of lead-free Bi2GeO5ferroelectric glass ceramics by thermal annealing - Puripat Kantha (2018)
To study the effect of thermal annealing on the electrical properties of lead-free Bi2GeO5ferroelectric glass ceramics, the glass ceramics with composition of Bi2GeO5were prepared by the conventional melt-quenching and heat-treatment methods subsequently. Glass ceramics of Bi2GeO5 was produced by subjecting the glasses from BiO1.5-GeO2-BO1.5system to the heat treatment schedule at 475°C for 18 h. After that, the resulting samples were separately annealed at 275 and 375°C for 4, 8, 12 and 18 h, respectively. The important properties of the annealed Bi2GeO5glass ceramics such as physical properties, phase formation and electrical properties were then investigated. It was found that the annealing treatment played an important role on electrical properties of these glass ceramics. The XRD patterns confirm the secondary phase of Bi4Ge3O12co-existed with Bi2GeO5which increased at higher annealing temperature and time. This caused a change in density and related electrical properties of the Bi2GeO5glass ceramics. Both annealing temperature of 275 and 375°C with various times can improve dielectric properties and ferroelectric behavior of the resulting Bi2GeO5glass ceramics when comparing with that of un-annealed sample. The optimum annealing temperature and time for the improvement of dielectric properties of Bi2GeO5glass ceramics was found at 375°C/12 h, where the maximum values of the dielectric constant (er) of 246 and low dielectric loss (tand) of 0.024 were obtained. Moreover, the ferroelectric property of all annealed glass ceramics exhibited the slim P-E loop and Pr values which slightly increased with increasing annealing temperature and time. However, the P-E loops are not the feature of truly ferroelectric, it may be represent a lossy capacitor behavior. Copyright © Taylor & Francis Group, LLC.